Overexpression of MutL homolog 1 and MutS homolog 2 proteins have reversed prognostic implications for stage I–II colon cancer patients - Shih-Chiang Huang; Shiu-Feng Huang; Ya-Ting Chen; Yu Chang; Yu-Ting Chiu; Il-Chi Chang; Hong-Dar Isaac Wu; Jinn-Shiun Chen (Biomedical Journal, 2017)
Background: The outcome of colon cancer patients without lymph node metastasis is heterogeneous. Searching for new prognostic markers is warranted. Methods: One hundred twenty stage I–II colon cancer patients who received complete surgical excision during 1995–2004 were selected for this biomarker study. Immunohistochemical method was used to assess p53, epidermal growth factor receptor, MLH1, and MSH2 status. KRAS mutation was examined by direct sequencing. Results: Thirty three patients (27.5%) developed metachronous metastasis during follow up. By multivariate analysis, only female gender (p = 0.03), high serum carcinoembryonic antigen (CEA) level (≧5 ng/ml) (p = 0.04), and MLH1 overexpression (p = 0.003) were associated with the metastasis group. The 5-year-survival rate were also significantly lower for female gender (71.7% versus 88.9%, p = 0.025), high CEA level (64.9% versus 92.4%, p < 0.001), and MLH1 overexpression (77.5% versus 94.4%, p = 0.039). In contrast, MSH2 overexpression was associated with better survival, 95.1% versus 75.5% (p = 0.024). Conclusions: The reversed prognostic implications in the overexpression of MLH1 and MSH2 for stage I–II colon cancer patients is a novel finding and worthy of further confirmation.